Cystic Lymphangioma of the Chest Wall: A Case Report - Norio Yokoigawa; Masashi Okuno; A.-H. Kwon (Case Reports in Gastroenterology, 2014)
Cystic lymphangioma is a congenital cystic malformation that occurs mostly in children. While it is mainly found in the cervix, cases in the chest wall are very rare. We report a case of cystic lymphangioma found in the chest wall of a 2-month-old girl. The patient was noted to have a tumor in the left chest wall at birth. Since it gradually increased in size, the patient was referred to our department. Transillumination and ultrasonography showed a cystic lesion in the left chest. Surgical resection was performed in one step. Histopathological examination showed a cystic lymphangioma.